A Cross-linguistic Perspective on Questions in German and French Adult Second Language Acquisition - Chilla, Solveig; Bonnesen, Matthias (Linguistik Online, 2012)
Several studies have been conducted to try and understand and explain the morphological and syntactic aspects of adult second language acquisition (SLA). Two prominent hypotheses that have been put forward concerning late L2 speakers' knowledge of inflectional morphology and of related functional categories and their feature values are the Impaired Representation Hypothesis (IRH) and the Missing Surface Inflection Hypothesis (MSIH). The cross-linguistic comparison of the acquisition of questions in German and French provided in this study offers a new perspective to differences and similarities between first language acquisition (FLA) and adult SLA. Comparing a Germanic and a Romance L2, differing not only in their overall linguistic properties (such as i. e. OV/VO, V2, clitics), but explicitly in the formation and regularities of questions, we present striking similarities in adult SLA, and irrespective of the first and the second languages and of instructed versus non-instructed learning. The investigation of the adult SLA of morphological and structural aspects of questions in French and German strengthens the assumption that the acquisition of morphology and syntax is connected in French and German FLA but is disentangled in adult SLA. Our data reveal variability of question syntax, and with the syntactic position of the verb in particular. Instead of discovering the correct position of the verb at a certain stage of acquisition which can be accounted for by parameter setting in FLA, the adult learners gradually approach the target word order but still exhibit a great deal of variation after several years of exposure to the L2. The findings provided here contradict the predictions of the MSIH (Prévost/White 2000; Ionin/Wexler 2002; among others), for not only morphological features, but syntactic finiteness of finiteness are problematic in adult SLA, and that the Impairment Representation Hypothesis (IRH) (Beck 1998; Eubank 1993/1994; among others) accounts for these differences in first and second language acquisition. IRH and FDH mirror our findings, by predicting the use of (domain-general) strategies instead of agreement or feature checking mechanisms.